Discrepant stakeholder perspectives on graduate employability strategies. Issue 5 (2nd September 2016) - Kinash, Shelley; Crane, Linda; Judd, Madelaine-Marie; Knight, Cecily
ABSTRACT: A literature review identified 12 strategies that have been empirically linked to improvements in graduate employability. A survey methodology was used to investigate self-reported use and/or perspectives on these strategies among four stakeholder groups. The following questions were asked: to students – What strategies are you using to improve your graduate employability; to graduates – What strategies did you use to improve your employability?; to higher education career development professionals and educators – Which of the following employability strategies do you provide for students?; and to employers – Which of the following strategies undertaken by students does your organisation value when recruiting graduates? Across the four stakeholder groups, 705 responses were received and analysed. The key findings were discrepancies between the strategies reported in the literature and those indicated in the surveys, as well as discrepancies between stakeholder groups in regard to which strategies were indicated.